Experimental Study Of Water Based Air Conditioning System For Space Cooling - Azmin, Abdul Rahman (Universiti Sains Malaysia, 2022)
Air conditioning system is a must in almost all residential area. There is various evaporative cooling technique that have been introduced to improve the performance of this basic appliances. However, cooling using the refrigerant whether it is synthetic or natural can still affect the environment. In this project, space cooling is intended by the mean of water-based air conditioning system. The air conditioning system will use a direct evaporative cooling system and water as refrigerant. The performance of the cooling system will be investigated through experiment. The air conditioning system using the direct evaporative cooling and water as refrigerant is built by modifying the current existence air conditioning system. The compressor in the condenser unit will be replaced with water pump to circulate the water inside the refrigerant cycle. While the direct evaporative cooling system will be retrofitted to the condenser unit to lower the temperature at the condenser air intake. Cooling media pad will be used to reduce the air temperature and improve the performance of the cooling system. The water volume flow rate inside the cooling coil is varied to investigate the performance enhancement. The experiment conducted will carry two main purposes. The first purpose is to measure the efficiency of the evaporative cooling system with different volume flow rate in the cooling coil. The second purpose of the experiment is to measure the performance of the cooling system. The experiment result shows that cooling system with water volume flow of 6.25×10-5m3 /s. has the highest efficiency of 44.83%. The experiment also shows the maximum and mean temperature difference of 6.56ᴼC and 4.62ᴼC respectively when the water volume flow rate in the pipe is 6.25×10-5 m3/s.